Molecular origin of asymmetric yield surface of crosslinked epoxy polymers - Jinyoung Kim; Kyeongmin Hong; Yong-Seok Choi; Dayoung Jang; Jang-Woo Han; Hyungbum Park (Polymer Testing)
In this study, we investigate the multiaxial mechanical behavior of thermosetting epoxy polymers and explore the asymmetry between tension and compression in their yield surfaces at the molecular level using molecular dynamics simulations, complemented by experimental validation through polymer synthesis. After constructing an atomistic-scale amorphous epoxy system based on molecular dynamics simulations, we derived equivalent stress–strain curves and yield surfaces as functions of the degree of crosslinking through biaxial deformation analysis. The results show that increasing the degree of crosslinking leads to an increase in equivalent stress in all loading directions, resulting in an expansion of the yield surface. Notably, a more accelerated expansion of the yield surface in the biaxial compression direction was observed at higher degrees of crosslinking, which is attributed to a deformation mechanism that more effectively accommodates stress in this loading direction. This unique deformation behavior is attributed to high non-bonded stress arising from reduced polymer chain mobility by crosslinking effect. To experimentally validate the deformation mechanisms, epoxy polymer samples were synthesized, and uniaxial tensile and plane-strain compression (PSC) tests were conducted to obtain stress–strain profiles and yield surfaces according to different degrees of cure. These results provide fundamental insights into the distinct mechanical properties of polymer materials, such as the asymmetry of the yield surface, by revealing their behavior at the molecular level.